2022
DOI: 10.1186/s12989-021-00445-8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmentally relevant concentrations of ambient fine particulate matter (PM2.5) depletes the ovarian follicle reserve and causes sex-dependent cardiovascular changes in apolipoprotein E null mice

Abstract: Background Fine particulate matter (PM2.5) exposure accelerates atherosclerosis and contains known ovotoxic chemicals. However, effects of exposure to PM2.5 on the finite ovarian follicle pool have hardly been investigated, nor have interactions between ovarian and cardiovascular effects. We hypothesized that subchronic inhalation exposure to human-relevant concentrations of PM2.5 results in destruction of ovarian follicles via apoptosis induction, as well as accelerated recruitment of primordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…The number of monocytes and Th17 cells was increased, and that of M0 macrophages and follicular CD4+ T cells was decreased in the female mice. This suggests that the difference in immune cell infiltration influenced by PM 2.5 is closely related to sex [57]. The increased monocyte and decreased M0 macrophage numbers in the female mice indicated that monocytes were recruited after exposure to PM 2.5 , and the phenotypic transformation of macrophages happened in the PM 2.5 -exposed female mice.…”
Section: Discussionmentioning
confidence: 89%
“…The number of monocytes and Th17 cells was increased, and that of M0 macrophages and follicular CD4+ T cells was decreased in the female mice. This suggests that the difference in immune cell infiltration influenced by PM 2.5 is closely related to sex [57]. The increased monocyte and decreased M0 macrophage numbers in the female mice indicated that monocytes were recruited after exposure to PM 2.5 , and the phenotypic transformation of macrophages happened in the PM 2.5 -exposed female mice.…”
Section: Discussionmentioning
confidence: 89%
“…28,29 More recent studies have found associations with brain cancers, 30 kidney and bladder cancers, 31 hepatocellular carcinoma, 32 breast cancer, 33 and overall cancer risk and mortality. [34][35][36] Animal studies have found PM 2.5 to cause ovarian dysfunction and damage via oxidative stress and inflammation through the nuclear factor kappa B (NF-κB)/interleukin 6 (IL-6) signalling pathway in mice, 37 trigger ovarian cell DNA double-strand breaks, as measured by immunofluorescent biomarkers in zebrafish, 38 deplete ovarian follicular reserve and decrease anti-Müllerian hormone concentrations in mice, 39,40 and induce a dose-response relationship between PM 2.5 levels and ovarian degeneration in mosquitoes. 41 To date, evidence for an association between air pollution and ovarian cancer risk has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Setarehbadi et al found that the distribution of ApoE genotypes was significantly different between fertile and infertile males 26 . The latest research found that inhalational exposure to PM2.5 could deplete the ovarian follicle reserve in female ApoE −/− mice 27 . However, there was few reports about the effects of PM2.5 on spermatogenesis in hyperlipidemia mice.…”
Section: Introductionmentioning
confidence: 99%
“…26 The latest research found that inhalational exposure to PM2.5 could deplete the ovarian follicle reserve in female ApoE À/À mice. 27 However, there was few reports about the effects of PM2.5 on spermatogenesis in hyperlipidemia mice. In the present study, ApoE À/À mouse, a mature animal model of hyperlipidemia, was used to investigate whether melatonin ameliorated PM2.5-generated spermatogenesis disorder in testes.…”
mentioning
confidence: 99%